Procesos administrativos del departamento de servicio de atención al cliente de la cadena de tiendas Metro en Trujillo. - Polo Acevedo, Ernesto Gerardo (2012)
This research is the analysis of administrative processes of the department of customer service in which it developed a business plan, contact and customer relationship, also, with the employees of the Tiendas Metro in the city of Trujillo. In this study, we considered seriously the theme of service, in order to understand and be able to establish parameters for the creation of a Service Model adapted to each organization which is involved in parallel see every administrative processes implemented and implemented within a Customer Service Department of a company product number (case study) and realize that the service itself is meaningless if not accompanied by adequate and well-evaluated business processes created. The above leads us to consider very carefully the processes of recruitment and selection of personnel for the service area, as not all people have the right skills that were previously applied to those occupying management positions, now the environment requires skills as patience, endurance, imagination, personal competence, friendliness and entrepreneurship. There has to assume that serve well is the key to organizational success and you can always improve customer service, even in societies apparently unwilling to do so. In the increasingly competitive world in which they develop business today, service is often what allows a company to beat in the market to other competitors, however great. Hardly organizations that disrespect their employees can encourage natural behavior of good customer relations without resorting to costly permanent supervision and what it means to be over people with more serious consequence: the loss of the best people and the fact that the company beyond just those with economic reasons. In the first chapter of this research, including the problematic reality, history and justification, the formulation of the problem under study, stating the problem statement, the definition and delimitation of the study object and justification of the problem, define the objective of the research both general and specific, which can visualize where you want to reach and what you want to do, as well as the theoretical framework that explains the theoretical basis underlying the research, which outlines concepts associated with: management services, administrative processes, indicators of administrative processes, marketing of services, service culture, customer orientation, recruitment and selection, service strategy, the moments of truth, external and internal customers , quality of service, to finally raise the hypothesis. In the second presents the research design, population and sample collection techniques, processing and analysis of data and the validity, reliability and how the results will be presented. The third part presents the results of the investigation. The fourth chapter presents the analysis and discussion of research results and finally highlights the findings and recommendations respectively.